Impact of Endoscopic Dacryocystorhinostomy on Sinonasal Quality of Life. Issue 5 (September 2016) - Miyake, Marcel M.; Gregorio, Luciano L.; Freitag, Suzanne K.; Lefebvre, Daniel R.; Gray, Stacey T.; Holbrook, Eric H.; Bleier, Benjamin S.
Background: Dacryocystorhinostomy (DCR) is the criterion standard of surgical treatment for complete nasolacrimal obstruction and dacryocystitis. There has been an expansion in the indication of the endonasal DCR (eDCR), but the impact of surgical manipulating an otherwise healthy nasal mucosa on postoperative sinonasal quality of life remains unknown. The purpose of this study was to determine whether patients who underwent eDCR experienced any decrement in sinonasal quality of life. Methods: A retrospective chart review of 44 patients who underwent eDCR between June 2012 and May 2015. The primary outcome was the total and nasal-specific domain 1 scores of the disease specific validated Sino-Nasal Outcomes Test 22. Preoperative scores were compared with the postoperative scores on days 0-30, 30-90, and 90-180 visits. A subgroup analysis of patients without nasal symptoms who underwent concomitant nasal surgical procedures was also performed. Results: A statistically significant increase was observed between the preoperative score and the first postoperative score (days 0-30) in both total (7.5 [0-44] to 24 [0-51], median [interquartile range]) and domain 1 (2.5 [0-11] to 9 [0-18]) scores (p = 0.0066 and p = 0.0001, respectively). In contrast, there was no statistically significant difference between the pre- and postoperative scores on days 30-90 or 90-180. Similar results were observed in the subgroup analysis. Conclusion: Analysis of our findings indicated that, in general, eDCR was well tolerated by patients and nasal symptom scores returned to baseline values within 30-90 days of surgery. The concomitant performance of septoplasty in the setting of asymptomatic septal deviation did not confer any long-term improvement in symptoms of nasal obstruction.